Discontented behavior among kindergarten girls students (Journal of the College of Basic Education, 2026)
This study aims to identify the behavior of resentment among female students of the Kindergarten Department at the College of Basic Education, Al-Mustansiriyah University, and to examine its forms, levels, and influencing factors. The research adopted a descriptive-analytical approach, and a structured questionnaire was administered to a randomly selected sample of students from different academic levels. The results revealed significant differences in resentment behavior according to the academic stage and social support. First-year students recorded higher levels of resentment compared to senior students. The most common manifestations of resentment were facial expressions, sighs, and momentary reactions, whereas explicit resentment appeared less frequently. The study concluded that resentment is closely related to academic and social pressures, highlighting the necessity of integrating psychological and emotional counseling programs to help students manage stressful situations and adopt positive emotional expression strategies.